Improved PageRank Algorithm for Web Structure Mining - Bama, Sathya; Ahmed, M.S.Irfan; Saravanan, A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The growth of internet is increasing continuously by which the need for improving the quality of services has been increased. Web mining is a research area which applies data mining techniques to address all this need. With billions of pages on the web it is very intricate task for the search engines to provide the relevant information to the users. Web structure mining plays a vital role by ranking the web pages based on user query which is the most essential attempt of the web search engines. PageRank, Weighted PageRank and HITS are the commonly used algorithm in web structure mining for ranking the web page. But all these algorithms treat all links equally when distributing initial rank scores. In this paper, an improved page rank algorithm is introduced. The result shows that the algorithm has better performance over PageRank algorithm.